2010
DOI: 10.1051/0004-6361/200913134
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-luminosity relation within individualFermigamma rays bursts

Abstract: We study the spectra of all long gamma ray bursts (GRBs) of known redshift detected by the Fermi satellite untill the end of July 2009. Their fluxes and fluences are large enough to allow a time dependent study of their spectral characteristics in the 8 keV-1 MeV energy range. We find that the peak energy E peak of their EL(E) spectrum correlates with the luminosity in a remarkably tight way within individual bursts. This time-resolved E peak − L iso correlation is very similar for all the considered bursts an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
155
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(190 citation statements)
references
References 57 publications
35
155
0
Order By: Relevance
“…The observation of an E pi -E iso relation in time-resolved spectra (e.g. Ghirlanda et al 2010;Frontera et al 2012;Basak & Rao 2012;Lu et al 2012) may also provide insights into the origin of the E pi -E iso boundary. Finally, Since the E pi -E iso relation is not an intrinsic property of GRBs, it may be difficult to use it to standardize GRBs (Ghirlanda et al 2006;Mészáros & Gehrels 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The observation of an E pi -E iso relation in time-resolved spectra (e.g. Ghirlanda et al 2010;Frontera et al 2012;Basak & Rao 2012;Lu et al 2012) may also provide insights into the origin of the E pi -E iso boundary. Finally, Since the E pi -E iso relation is not an intrinsic property of GRBs, it may be difficult to use it to standardize GRBs (Ghirlanda et al 2006;Mészáros & Gehrels 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A key feature of gamma-ray bursts (GRBs) is the observed relation within a burst between the luminosity and the νFν peak energy (E rest peak ) (Golenetskii et al 1983;Kargatis 1994;Borgonovo & Ryde 2001;Ryde et al 2006;Ghirlanda et al 2010;Lu et al 2010;Zhang & Chen 2012;Guiriec et al 2013;Burgess et al 2014). This luminosity-E rest peak relation was first discovered by Golenetskii et al (1983) and has been found in several GRBs regardless of their lightcurve shape.…”
Section: Introductionmentioning
confidence: 99%
“…Other attempts to explain the observed GCs invoked non-thermal synchrotron emission (Zhang & Meszaros 2002;Dermer 2004) in both single (Ghirlanda et al 2010) and multi-component Preece et al 2014) time-resolved spectra. For synchrotron emission, one expects L ∝ NeB 2 Γ 2 γ 2 e and E peak ∝ BΓγ 2 e where Ne is the number of emitting electrons, B in the magnetic field, γe is the characteristic electron Lorentz factor and Γ is the bulk Lorentz factor.…”
Section: Introductionmentioning
confidence: 99%
“…These two correlations were then used to create a GRB Hubble diagram (Schaefer 2003). Other luminosity and energy correlations were soon discovered, such as: the Amati relation (Amati et al 2002;Amati 2006;Amati et al 2008Amati et al , 2009) which relates the intrinsic spectral peak energy, E p,i , to the equivalent isotropic energy, E iso ; the Yonetoku relation (Yonetoku et al 2004) which is a correlation between E p,i and the isotropic peak luminosity, L iso ; the Ghirlanda relation (Ghirlanda et al , 2006(Ghirlanda et al , 2010 which is a correlation between E p,i and the collimation corrected energy E γ ; and the Liang-Zhang relation (Liang and Zhang 2005) which relates E iso to both E p,i and the break time of the optical afterglow light curves, T a .…”
Section: Introductionmentioning
confidence: 99%